Evaluation of effective factors on theoretical classes' attendance of dentistry students of Babol University of Medical Sciences - Maryam Seyedmajidi; Kambiz Naderi; SeyedAli Seyedmajidi (Babol University of Medical Sciences, 2017)
BACKGROUND AND OBJECTIVE: The characters and roles of teachers and demographic characteristics and attendance of students have special places in classroom. Students are interested to participate in classroom logically and manner of faculty members' teaching manner determine students' attendance in class. This study aimed to investigate the factors influencing the students' attendance in theoretical classes from the perspective of dental students of Babol Dentistry School. METHODS: This descriptive-analytical research was carried out as a cross-sectional study in 2015-2016 academic year. Sampling was performed by census method. Data collection tool was a questionnaire consisted of two parts of demographic data and 21 items in three fields of teacher, student and physical environment. To analyze the data, SPSS version 16 software was used and the significance level of 0.95 was considered. FINDINGS: From the perspective of dental students, the teacher field was mentioned as the most effective factor and physical environment field had the least impact on the attendance of students in theoretical classes. The differences of mean scores of physical environment field in comparison with teacher and student fields (p-value<0.0001) and between male and female participants (p-value=0.006) were statistically significant. Among the participants from various enterance years, the highest and the lowest average scores were related to 2010 and 2015 enterance years. CONCLUSION: Relationships between students and teachers and the interactions among them are associated with positive behavioral and attitudinal results for students. Educational authorities should create a high-quality learning environment, implement modern methods of teaching and dealing with students to teachers and encourage students to participate in classrooms.